Transcript-dependent effects of the CALCA gene on the progression of post-traumatic osteoarthritis in mice - Shan Jiang; Weixin Xie; Paul Richard Knapstein; Antonia Donat; Lilly-Charlotte Albertsen; Jan Sevecke; Cordula Erdmann; Jessika Appelt; Melanie Fuchs; Alexander Hildebrandt; Tazio Maleitzke; Karl-Heinz Frosch; et al. (Communications Biology, 2024)
Abstract Osteoarthritis represents a chronic degenerative joint disease with exceptional clinical relevance. Polymorphisms of the CALCA gene, giving rise to either a procalcitonin/calcitonin (PCT/CT) or a calcitonin gene-related peptide alpha (αCGRP) transcript by alternative splicing, were reported to be associated with the development of osteoarthritis. The objective of this study was to investigate the role of both PCT/CT and αCGRP transcripts in a mouse model of post-traumatic osteoarthritis (ptOA). WT, αCGRP −/− and CALCA −/− mice were subjected to anterior cruciate ligament transection (ACLT) to induce ptOA of the knee. Mice were sacrificed 4 and 8 weeks post-surgery, followed by micro-CT and histological evaluation. Here we show that the expression of both PCT/CT and αCGRP transcripts is induced in ptOA knees. CALCA −/− mice show increased cartilage degeneration and subchondral bone loss with elevated osteoclast numbers compared to αCGRP −/− and WT mice. Osteophyte formation is reduced to the same extent in CALCA −/− and αCGRP −/− mice compared to WT controls, while a reduced synovitis score is noticed exclusively in mice lacking CALCA. Our data show that expression of the PCT/CT transcript protects from the progression of ptOA, while αCGRP promotes osteophyte formation, suggesting that CALCA-encoded peptides may represent novel targets for the treatment of ptOA.